‘Upright, Whole, and Free': Eschatological Union with God - Timpe, Kevin (TheoLogica, 2018)
In the closing canto of the Purgatorio in his Divine Comedy, Dante Alighieri describes the souls preparing to enter heaven as "new, remade, reborn, … perfect, pure, and ready for the Stars [i.e., heaven]." But what exactly would it mean for a human soul to be morally perfect and in perfect union with the divine will? Furthermore, if the soul fit for heaven is perfectly united with God, what sense does it make to think that individual retains their free will? In this talk, I assume a number of Christian claims about the Beatific Vision and argue that not only do the souls fit for heaven retain their freedom, but that they are in sense ‘more free' despite their inability to do certain actions.